Anatomic based microfracture technique of insertion for rotator cuff repair in Vietnamese people: Case series study - Trung, Dung Tran; Huu, Manh Nguyen; Tran, Quyet; Duc, Vu (Annals of medicine and surgery, 2021)
Postoperative tendon healing is still a matter of concern after rotator cuff repair. Several techniques have been introduced to help improve this healing process. Among them, the bone marrow is commonly used source and a research subject for methods using stem cells to promote wound healing process. A number of studies have shown that bone marrow stem cells can travel up through the holes on the rotator cuff insertion sites, contributing into the rotator cuff repair process, increasing the efficiency of tendon healing and improving clinical results. Cross-sectional descriptive study was performed on 41 rotator cuff tear patients. The microfractures for these patients were calculated beforehand, which have great depth but small diameter, based on the anatomical characteristic of the rotator cuff tear insertions of Vietnamese people. Patients' rotator cuff tendon healing processes were evaluated using ultrasound after surgery. Final tendon healing and clinical results ultimately rely on MRI assessments, classified according to Sugaya's classification, UCLA and ASES scale. No cases of rupture and fracture of the greater tubercle was recorded. There was a clear progression of tendon healing on ultrasound according to postoperative follow-up time-stamps (1 month, 3 months). MRI images evaluation also reveals at the latest follow-up time, according to Sugaya classification, the ratio of tendon healing was 87.8%, while the percentage of re-rupture was 12.2%. ASES and average UCLA scale were collected at the end of the study, respectively as 95.41 ± 5.45 and 32.36 ± 2.53. The technique's microfractures characteristics based on the rotator cuff tear insertion anatomy ensures a secure, straightforward approach along with promising results in terms of tendon healing rate and postoperative functional outcomes.